Temporal geospatial shorelines changes analysis in Klang Coastal Area - Ibrahim, Illyani; Asmawi, M. Zainora; Jaafar, Samsuddin (2016)
The coastal area of Klang at the eastern of Malaysia contains different types of land covers that are surrounded by the urban and mangroves areas. These areas are significant for environmental biodiversity. This article focuses on the erosion along the Kapar to Jeram coastal areas. The purpose of this study is to monitor the 41 years of shoreline changes using satellite imageries from 1974 to 2015 (Landsat TM and ETM+). The coastline is delineated by using the histogram slicing technique. One hundred transects were sampled at 200 meter intervals along the shoreline. The transects were obtained by calculating the rate of change of mangrove shorelines and distance. Finding shows that an average for the shoreline rate of change was 5 m/year . The results of this study will be translated to propose a policy for environmental mitigation. The outcome of this study will introduce the proposed environmental mitigation for future planning in the specific sectors of coastline.